2018
DOI: 10.1111/pce.13195
|View full text |Cite
|
Sign up to set email alerts
|

UPLC‐HRMS‐based untargeted metabolic profiling reveals changes in chickpea (Cicer arietinum) metabolome following long‐term drought stress

Abstract: Genetic improvement for drought tolerance in chickpea requires a solid understanding of biochemical processes involved with different physiological mechanisms. The objective of this study is to demonstrate genetic variations in altered metabolic levels in chickpea varieties (tolerant and sensitive) grown under contrasting water regimes through ultrahigh-performance liquid chromatography/high-resolution mass spectrometry-based untargeted metabolomic profiling. Chickpea plants were exposed to drought stress at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
139
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 200 publications
(159 citation statements)
references
References 113 publications
17
139
1
2
Order By: Relevance
“…A growing number of studies have reported the accumulation of allantoin in plants as a response to various stress conditions; allantoin participates in plant stress responses and provides tolerance to abiotic stress factors [76][77][78]. Similar findings in chickpea under drought stress have been reported [79].…”
Section: Allantoin Accumulation Is Related To Salt Tolerancesupporting
confidence: 66%
“…A growing number of studies have reported the accumulation of allantoin in plants as a response to various stress conditions; allantoin participates in plant stress responses and provides tolerance to abiotic stress factors [76][77][78]. Similar findings in chickpea under drought stress have been reported [79].…”
Section: Allantoin Accumulation Is Related To Salt Tolerancesupporting
confidence: 66%
“…Abiotic stresses are the most damaging for plants, among these the most destructive that effect the plants from physiological to molecular level is drought stress that limiting the growth and yield of crop plants ( Khan et al 2018;Pereira and Chaves 1995). It is estimated that drought stress may cause a 50% loss in crop plants (Kasim et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Arginine is also a precursor for nitric oxide and polyamines, which are important metabolites in stress responses 52 . For example, high arginine accumulation in response to long-term drought stress was also observed in chickpea 53 . Intriguingly, we observed a strong accumulation of DL-arginine in the ripe fruit of both species, but further studies are needed to assess whether this may be related to abiotic stress adaptation in both species.…”
Section: Discussionmentioning
confidence: 90%